Tradisi unik dalam budaya Lamongan: Wanita yang melamar pria menurut adat lokal - zubaidah, siti zubaidah (Maliki Interdisciplinary Journal, 2025)
This research aims to uncover unique customs in the Lamongan area where women have an active role in the process of selecting their life partner. In Lamongan society, the tradition of proposing which is usually carried out by men has undergone a change where women have the freedom to propose to the man of their choice. The research was carried out using a qualitative approach through interviews with key informants in the Lamongan area. The research results show that this unique custom in the Lamongan area is a reflection of the gender equality that occurs in that society. Women in Lamongan have the freedom to express their interests and feelings towards the men they want without being bound by rigid patriarchal traditions. This shows that in Lamongan society, the role of women in the process of finding a life partner is considered as important as that of men. This research contributes to further understanding of the dynamics of culture and customs in the Lamongan area, and also highlights the importance of gender equality in interpersonal relations in society. Apart from that, this research can also be an inspiration for other communities to accept the positive social changes occurring in their society, as well as strengthen the values ​​of equality and individual freedom.